Acrylamide Influence on Activity of Acetylcholinesterase, Thiol Groups, and Malondialdehyde Content in the Brain of Swiss Mice. Issue 10 (16th June 2015) - Kopańska, Marta; Lukáč, Norbert; Kapusta, Edyta; Formicki, Grzegorz
ABSTRACT Acrylamide is a neurotoxin inhibiting neurotransmission in peripheral nerves. Less is known about acrylamide influence on the central nervous system. Here we measured acrylamide influence on the acetylcholinesterase activity in brain stem, hemispheres, and cerebellum of mice (males, Swiss strain) in relation to the thiol groups and malondialdehyde concentration. Acrylamide was injected intraperitoneally (20 and 40 mg/kg, i.e. 0.52 and 1.04 mg per animal). The brain structures were taken 24, 48, and 192 h after the injection. Acetylcholinesterase activity was significantly lower (p < 0.001 to p < 0.05) in all the structures. It was accompanied by the statistically significant (p < 0.001 to p < 0.05) increase in malondialdehyde concentrations in most of the studied structures time periods and ACR doses. –SH groups concentrations were significantly depleted in the right hemisphere (p < 0.01) after 24 h and in brain stem (p < 0.05) after 48 h. We suggest that neurotoxicity of acrylamide in brain is related to acetylcholinesterase inhibition and redox imbalance.